The student's encyclopedia of Judaism - Skolnik, Fred; Wigoder, Geoffrey (New York (N.Y.) New York University press, 2004)
Identifies and defines people, places, and terms important to the Jewish faith.
Keywords: Judaism -- Dictionaries -- Juvenile literature; Judaism -- Dictionaries